Artefak Budaya Jawa Dalam Sistem Kebudayaan Nusantara - Dharsono Dharsono (Ornamen, 2006)
Culture represent the overall of idea system, action and result are masterpiece of human being in life society. Form and content of culture, according to anthropologist at least has three forms (1) ideas, (2) activities and (3) artifacts. The form of culture are interactive each other. The most abstract system (ideas) looks like stay in the top of system to arrange social system activity more concrete, while the activities in social system yield the material culture (artifact). To ask about Nusantara fine arts, it will not release the Nusantara artifact culture result. Nusantara artifact culture in Java societies represent the expression of Java culture according to the philosophy and the culture system of values its self.Keyword: culture, philosophy,